Smoking ban and health at birth - Tamás Hajdu; Gábor Hajdu (Hungarian Academy of Sciences, Institute of Economics, 2017)
In 2012, smoking restrictions were extended to hospitality venues in Hungary. Women working in bars and restaurants were primarily affected by the intervention. In this research, we analyze the effect of this smoking ban on the outcomes of their intended pregnancies. Using complete individual live birth, fetal loss (miscarriage, stillbirth), and infant mortality registry data, we examine the probability of live birth, indicators of health at birth, and the probability of death in the first year of life. We perform a difference-in-differences estimation and show that the smoking ban has improved health at birth of the newborns of mothers working in bars and restaurants and has reduced infant mortality among them. Performing a series of robustness tests, we provide evidence that strongly supports the causal interpretation of our results. We also show that the ban was more beneficial for newborns of parents with low educational attainment and with lower fetal health endowments.
Keywords: I18; J13; 330; smoking ban; policy evaluation; health at birth